Membaca Masa Depan Ekonomi-Bisnis Metropolitan: Refleksi untuk Semarang dari Telaah Bibliometrik Global Berbasis Metadata Scopus - Muhammad Alfarizi; Ngatindriatun Ngatindriatun; Isti Widiharjanti (Jurnal Riptek, 2025)
Metropolitan areas such as Semarang play a strategic role in driving regional and national economic growth. However, comprehensive insights into the city's economic-business future remain limited. This study aims to map global research trends related to urban economic-business issues through a Systematic Literature Review (SLR) combined with bibliometric analysis, using Scopus metadata as the primary source. Employing the PRISMA framework, the study analyzed 93 relevant documents (20092024) with the support of Bibliometrix R and VOSviewer software. The results show a significant increase in global academic attention to urban economic topics, particularly concerning sustainability, MSME digitalization, public sector governance transformation, and strategic leadership. Four major thematic clusters were identified: (1) consumer behavior and value-based business practices, (2) public organizational culture and digital entrepreneurship, (3) digital innovation and competitive social capital in MSMEs, and (4) green leadership and sustainable urban governance. Keyword co-occurrence visualization highlighted the prominence of themes such as sustainability, circular economy, and competitive advantage in global research narratives. The study emphasizes the need to integrate technology, local values, and collaborative governance to formulate adaptive and knowledge-based development strategies. Furthermore, the global bibliometric findings serve as a conceptual foundation for envisioning the future trajectory of Semarang's economic-business landscape, offering reflective insights for policymakers, academics, and entrepreneurs aiming to enhance the city's competitiveness and sustainability.